Survey of wormhole attack in wireless sensor networks - Ghugar, Umashankar; Pradhan, Jayaram (Computer Science and Information Technologies, 2021)
From the last decade, a wireless sensor network (WSN) has a very important role over the networks. The primary features of WSN include satellite communication, broadcast channel, hostile environment, medical system and data gathering. There are a lot of attacks available in WSN.In wormhole attack scenario is brutal from other attacks, which is smoothly resolved in networks but tough to observe. This survey paper is an experiment to observing threats and also focuses on some different method to identify the wormhole attacks.